Knowledge, attitudes, and practices towards cervical cancer screening among health students: a case of Kenya Medical Training College - Mutuku, Faith M.; Otieno, Careena; Midigo, Ronnie (International Journal Of Community Medicine And Public Health, 2025)
Background: Cervical cancer is the fourth most diagnosed cancer and fourth leading cause of cancer mortality among women globally. In developing countries, it is the second most common cancer and the leading cause of cancer deaths among women. In Kenya, 33 per 100,000 women have cervical cancer and 22 per 100,000 succumb to the disease. Despite being preventable, through screening and treatment of premalignant lesions, screening is however not readily utilized in most developing countries, including Kenya. This study aimed to assess health students’ knowledge, attitude and practices on cervical cancer screening. Methods: Descriptive cross-sectional study design was conducted among 354 female Kenya Medical Training College students using a self-administered questionnaire. Data analysis was done using Statistical Package for Social Sciences (SPSS) version 25. Scores for knowledge and attitude were computed as either poor, fair or good. Results: Over half of the respondents 213 (60%) had low knowledge of cervical cancer risk factors and only 35 (10%) had ever been screened. Majority 272 (76%) had good attitude towards screening. Conclusions: The study showed that screening is influenced by knowledge and attitude. Students with good knowledge and attitude were more likely to screen, but overall screening rates remain low. Developing tailored screening programs for health students are recommended to increase screening rates.